Anionic Co‐insertion Charge Storage in Dinitrobenzene Cathodes for High‐Performance Aqueous Zinc–Organic Batteries. Issue 35 (19th July 2022) - Song, Ziyang; Miao, Ling; Duan, Hui; Ruhlmann, Laurent; Lv, Yaokang; Zhu, Dazhang; Li, Liangchun; Gan, Lihua; Liu, Mingxian
Abstract: Highly active and stable cathodes are critical for aqueous Zn–organic batteries with high capacity, fast redox kinetics, and long life. We herein report para ‐, meta ‐, and ortho ‐dinitrobenzene ( p ‐, m ‐, and o ‐DB) containing two successive two‐electron processes, as cathode materials to boost the battery performance. Theoretical and experimental studies reveal that nitro constitutional isomerism is key to zincophilic activity and redox kinetics. p ‐DB hosted in carbon nanoflower harvests a high capacity of 402 mAh g −1 and a superior stability up to 25 000 cycles at 5 A g −1, giving a Zn–organic battery with a high energy density of 230 Wh kg −1 . An anionic co‐insertion charge storage mechanism is proposed, entailing a two‐step (de)coordination of Zn(CF3 SO3 ) + with nitro oxygen. Besides, dinitrobenzene can be electrochemically optimized by side group regulation via implanting electron‐withdrawing motifs. This work opens a new window to design multielectron nitroaromatics for Zn–organic batteries. Abstract : Anionic co‐insertion charge storage in dinitrobenzene cathodes is reported, which entails two successive coordination/decoordinations of Zn(OTF) + complex with the nitro oxygen. The nitroaromatic multielectron chemistry contributes to ultrahigh capacity, fast redox kinetics, and superior cycle stability for the assembled aqueous Zn–organic battery.